The EU Response to the Presence of Nitrosamine Impurities in Medicines - Ruepp, Robin; Frötschl, Roland; Bream, Robert; Filancia, Maria; Girard, Thomas; Spinei, Andrei; Weise, Martina; Whomsley, Rhys (Frontiers in Medicine, 2021)
The unexpected detection of nitrosamine impurities in human medicines has recently seen global regulators act to understand the risks of these contaminations to patients and to limit their presence. Over 300 nitrosamines are known, many of which are highly potent mutagenic carcinogens. Regulators first became aware of the presence of nitrosamines in EU medicines in 2018, with reports of detection of NDMA in valsartan from one manufacturer. A subsequent EU review of all valsartan medicines was triggered by the European Medicines Agency (EMA) and was later extended to other sartan medicines, a separate review was also started for ranitidine medicines. This was followed by an EU-wide examination of the risk of presence of nitrosamines in all human medicines. This article reflects on the EU regulatory network’s investigation into the presence of nitrosamines and the scientific knowledge informing recommendations for developers on how to limit nitrosamines in medicines.